Hell on Earth 2024: Metaphors of Genocide in the Gaza Strip, Palestine - Vannisa Najchati Silma; Hermina Sutami (Journal of Language and Literature, 2025)
Metaphors play a crucial role in shaping how society understands and responds to conflicts, such as the genocide in Gaza by Israel. Metaphors can illustrate the impact of events, direct global attention to injustices, and deepen the understanding of the scale and intensity of the humanitarian crisis in the region in a way that is more easily comprehensible. In the international media coverage of Al-Jazeera, metaphorical expressions are often used to describe Israel’s attacks and the suffering that occurred in the Gaza Strip, Palestine. The purpose of this study is to explain the concepts produced from the use of metaphorical expressions related to Israel’s genocide in the Gaza Strip in Al-Jazeera news articles. This study applies Lakoff and Johnson's conceptual metaphor theory and Charteris-Black's critical metaphor analysis. Based on the analysis, four metaphorical concepts of the Gaza genocide were identified: ISRAEL’S AGGRESSION IS GAZA’S GENOCIDE, THE GAZA GENOCIDE IS A CATASTROPHE, PALESTINIANS ARE NOT HUMAN, and GAZA IS A GHOST TOWN. The metaphor concepts depict a social reality schema in the form of identity, force, scale, and unity/multiplicity that reflects the social reality of violence, oppression, and dehumanization. The four metaphor concepts show the process of Israel’s attacks, a depiction of life in the Gaza Strip, the dehumanization of Palestinians, and the impact of Israel’s genocide on Gaza. These are closely related to Israel’s colonialism practices which aim to control the region through occupation, land stealing, and the erasure of Palestinian identity and rights.